Pelaksanaan Rehabilitasi Sosial Terhadap Warga Binaan Pemasyarakatan Narkotika Pada Lembaga Pemasyarakatan Kelas II A Ambon - Sofyan, Ode; Adam, Sherly; Patty, Jetty Martje (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Rehabilitation is an effort to restore and restore the condition of drug users to return to physical, psychological, social, and spiritual/religious health (faith). With the condition after undergoing rehabilitation, it is hoped that they will be able to return to live in the midst of society better and be free from narcotics bondage. The Narcotics Law has regulated the implementation and obligation of rehabilitation written in Article 4, Article 54, Article 55, Article 103, and Article 127 of the Narcotics Law which regulates the rehabilitation of victims of narcotics abuse, narcotics addicts, and narcotics abusers and is often also in the spotlight in its law enforcement practices.Narcotics abuse is one of the biggest crimes faced by the Indonesian people. In order to address this issue, the Government has issued a regulation, namely Presidential Instruction Number 2 of 2020 concerning the National Action Plan for the Prevention and Eradication of Abuse and Illicit Trafficking of Narcotics and Narcotics Precursors (RAN P4GN) 2020/2024. To succeed the program, the Ministry of Law and Human Rights of the Republic of Indonesia organizes a rehabilitation program for prisoners who abuse drugs in correctional institutions with the basis for its implementation, namely Law Number 22 of 2022 concerning Corrections, the Narcotics Law and other related regulations. The purpose of the program is not only to prevent drug abuse and illicit trafficking, but also to enable drug addicts to resume their social functions in the community. Cases of criminal acts and drug abuse in Class II A Ambon Correctional Institution (hereinafter referred to as Class II A Ambon Correctional Institution) committed by correctional inmates are inseparable from the issue of demand and supply of narcotics. The data shows that the number of prisoners (WBP) of narcotics cases in Class II A Ambon Correctional Facility in 2021 amounted to 40 prisoners and in 2022 amounted to 40 prisoners.Purposes of the Research: Analyze and discuss the obstacles faced in the implementation of social rehabilitation of prisoners of narcotics correctional facilities at Class II A Ambon Correctional Facility.Methods of the Research: The research method used with the type of Empirical juridical research. The research location is class II A Ambon correctional institution, Data sources are primary data and secondary data. Data collection techniques through observation and interviews. Data processing techniques and data analysis in culaitative. Results / Findings / Novelty of the Research: The results showed that there are several obstacles that influence the implementation of social rehabilitation of narcotics wargabinan at the Klas IIA Ambon Correctional Institution. These obstacles have an effect on the implementation of social rehabilitation of narcotics wargabinan carried out at the Klas IIA Ambon Correctional Institution. This condition causes a lack of maximum implementation of rehabilitation at the Klas IIA Ambon Correctional Institution. The obstacles faced in the implementation of social rehabilitation of prisoners of narcotics correctional facilities at Class II A Ambon Correctional Facility are facilities or facilities, human resources or officers and budget or costs